Brewing property in one-dimensional city? Exploring Starbucks’ locational strategies-impacts in the case of Izmir, Türkiye - Aşçı Coşkun, Yağmur; Penpecioğlu, Mehmet (Estoa. Journal of the Faculty of Architecture and Urbanism, 2026)
The article examines Starbucks’ locational strategies and their impact on urban spaces, drawing on Rossi’s concept of the “one-dimensional city.” As global brands increasingly shape urban environments, three key effects emerge: rising property prices near stores, the concentration of locations in malls, transit hubs, and walkable areas, and alignment with urban landscapes standardized by major transportation infrastructure decisions. Similar to many cities in the Global South, Starbucks in İzmir functions both as a product and a driver of property-driven, rent-seeking urban development. Empirical evidence reveals that its locational strategies enhance accessibility, increase property values, and reshape the built environment. Through spatial analysis, the article examines Starbucks locations within a walkability and accessibility framework, highlighting their concentration in high-value districts with strong public transit connections. This research underscores how global brands reinforce socio-economic divides, transform urban spaces, and promote consumption-driven urbanization through their integration into global capitalism and real estate dynamics.